T Cell engineering for cancer immunotherapy by manipulating mechanosensitive force-bearing receptors - Zhao, Lingzhu; Zhao, Guoqing; Feng, Jinteng; Zhang, Zheng; Zhang, Jiayu; Guo, Hui; Lin, Min (Frontiers in Bioengineering and Biotechnology, 2023)
T cell immune responses are critical for in both physiological and pathological processes. While biochemical cues are important, mechanical cues arising from the microenvironment have also been found to act a significant role in regulating various T cell immune responses, including activation, cytokine production, metabolism, proliferation, and migration. The immune synapse contains force-sensitive receptors that convert these mechanical cues into biochemical signals. This phenomenon is accepted in the emerging research field of immunomechanobiology. In this review, we provide insights into immunomechanobiology, with a specific focus on how mechanosensitive receptors are bound and triggered, and ultimately resulting T cell immune responses.